18F-fluorodeoxyglucose uptake on PET/computed tomography in association with androgen receptor expression and other clinicopathologic factors in surgically resected triple-negative breast cancer. Issue 1 (January 2021) - Lee, Hyo-jae; Lim, Hyo Soon; Ki, So Yeon; Park, Hye Mi; Lee, Jong Eun; Jeong, Won Gi; Shin, Sang Soo; Kwon, Seong Young; Park, Min Ho; Lee, Ji Shin
Abstract : Objective: To evaluate whether androgen receptor expression in triple-negative breast cancer (TNBC) is associated with 18 F-fluorodeoxyglucose (FDG) uptake and to identify predictive factors of 18 F-FDG uptake in TNBC. Methods: We retrospectively assessed data of 156 surgically resected primary TNBC in 156 consecutive patients who underwent 18 F-FDG PET/computed tomography between July 2013 and May 2017. Clinicopathologic features, including androgen receptor expression, were categorized and the distribution of maximum standardized uptake value (SUVmax ) was compared between the groups. We also evaluated the correlations between the predictive factors and SUVmax . Results: Median SUVmax was higher in the androgen receptor-negative group than in the androgen receptor-positive group (8.8 vs. 7.1, P = 0.026) with negative correlation between androgen receptor and SUVmax ( P = 0.041, correlation coefficient ( r ) = –0.163). On multivariate regression analysis, tumor size (>20 mm), histological grade, Ki-67 (≥14%), and the presence of ductal carcinoma in situ (DCIS) were significantly associated with SUVmax ( P < 0.001, P = 0.012, P = 0.017 and P = 0.021, respectively). Tumor size, histological grade and Ki-67 were positively correlated with SUVmax ( P < 0.001, r = 0.450; P = 0.004, r = 0.228; P = 0.001, r = 0.269, respectively), while the presence of DCIS showed negative correlation with SUVmax ( P < 0.001, r = –0.292). Conclusion: Androgen receptor-positive TNBC showed lower 18 F-FDG uptake than androgen receptor-negative triple-TNBC. Tumor size, histological grade, Ki-67 and the presence of DCIS significantly influenced 18 F-FDG uptake in TNBC.